THE EFFECT OF RED GINGER RELEASE CONSUMPTION (Zingiber officinale var. Rubrum) AGAINST DISMENORE IN ADOLESCENT HIGH SCHOOL - Kusila Devia Rahayu; Ivon Guite; Haidir Syafrulloh (Journal of Maternity Care and Reproductive Health, 2018)
Dysmenorhea can be experienced by every woman who is menstruating. Teenagers are an age group that is prone to dysmenorhea. A preliminary study found that of 125 high school teenagers in the city of Bandung 90 of them experienced dysmenorrhea. The results of the interviews revealed various ways they performed when dysmenorrhea included rest, rubbing the stomach, consumption of young coconut water, analgesic drugs and red ginger. Red ginger or Zingiber officinale var. Rubrum is a type of spice that grows and is known as complementary ingredients in Indonesia. The purpose of this study was to determine the effect of consumption of red ginger stew on dysmenorrhea in high school adolescents. This type of research is quasi-experimental with non equivalent control group design. Data collection was carried out by purposive sampling on 54 respondents. The instrument in this study uses a Numeric Rating Scale sheet. Data analysis was carried out using The Wilcoxon test with a p-value of 0.000 (≤ α). The results of the study revealed that the administration of red ginger stew affected dysmenorrhea in high school adolescents. Health workers are advised to promote red ginger stew as a complementary therapy to overcome juvenile dysmenorrhea by involving officers in the School Health Unit.